ANTIOXIDANT AND ANTIFUNGAL EFFECT OF FRESH GINGER (Zingiber officinale) ON THE SHELF-LIFE OF SMOKED CATFISH - ABUBAKAR, M. I.; ADESHINA , I.; OGUNNIRANN, G.; ABDULRAHEEM, I.; EZERIG , N. O.; OMONIYI, I.T. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The antioxidant and antifungal effects of ginger paste extracted from fresh ginger on smoked catfish were examined for a 21-day storage period at room temperature (25-30oC). The ginger paste was extracted from fresh ginger by scrapping off the outer coat, ground and blended.  Eighty fish samples were gutted and washed thoroughly after which they were divided into five groups of sixteen. Each group was spiced with ginger paste at 10g, 20g, 30g and 40g respectively while the control batch was not spiced. The fishes were then smoked in a smoking kiln for 8hrs. The Superoxide dismutase activity and fungal isolation analyses were carried out to investigate the antioxidant and antifungal effect of ginger paste on the fish samples. The lowest superoxide dismutase and peroxide values (0.64 ?/mg and 7.483 mEq/kg respectively) were recorded in the group of catfish spiced with 40g of ginger (at day 21) and control respectively while the highest Superoxide Dismutase (1.92 ?/mg) and Peroxide (9.141 mEq/kg) values were recorded in the group of catfish spiced with 30g of ginger at Day 21. Mucor circinelloides, Rhizopus stolonifer and Aspergillus niger were isolated from the spiced catfish samples The result revealed that catfish samples spiced with ginger paste had lowest mould count compared with the control group. Recommendation was made for the use of 30-40g of ginger to spice 1kg of catfish in order to reduce microbial growth on them.